Factor Matrix of Millennial and Gen-Z Generations on Money Politics in Elections in Lubuklinggau City: Matrik Faktor Generasi Milenial dan Gen-Z terhadap Money Politik dalam Pemilu di Kota Lubuklinggau - Muhammad Dimas Rizqi; Mardi Murahman; Wilika Nabila; Andhico Mardha Giovani (Universitas Indo Global Mandiri, 2026)
Purpose : This study analyzes the factors influencing the behavior of Millennials and Generation Z toward money politics in the 2024 General Election in Lubuklinggau City. Design/methodology/approach : With young voters dominating the electoral landscape, this research employs a qualitative case study approach through interviews, observations, Focus Group Discussions (FGD), and document analysis, supported by NVivo12 Plus. Findings : The findings reveal six main factors shaping youth attitudes: political education, practical political experience, values and ideology, technology and social media, economic conditions, and peer influence. NVivo analysis highlights political education as the most dominant factor, followed by economic conditions and peer groups. Practical Implication : These results underscore the urgency of strengthening political education, enhancing digital literacy, and improving economic conditions, particularly in youth-dominated areas, as strategies to reduce money politics and foster more critical, rational, and integrity-based political participation among young voters. Originality/value : Providing new findings, especially in handling political money actions or practices for young people in dominant areas.